The impact of malaria on the immunogenicity and efficacy of mycobacterium bovis BCG vaccination against mycobacterium tuberculosis in mice - Tangie, Emily Nchangnwie (Department of Clinical Laboratory Sciences, 2022)
Background Bacillus Calmette-Guerin (BCG) remains the only licensed vaccine for use against tuberculosis (TB), however, it is poorly efficacious against pulmonary TB in adults. The poor efficacy has been attributed in part to coinfections with many other unrelated pathogens that overlap geographically with Mycobacterium tuberculosis (M. tuberculosis). In this study, we used a murine model to investigate the effect of Plasmodium species virulence and the timing of infection on BCG-induced immune responses and efficacy against M. tuberculosis both in vivo by aerosol challenge and ex vivo by Mycobacterial Growth Inhibition Assay (MGIA). Methods and Results To assess the impact of malaria parasite virulence on BCG, wild-type C57BL/6 mice were vaccinated intraperitoneally with BCG Pasteur and 6 weeks later, they were infected with either virulent Plasmodium berghei (P. berghei) or less-virulent Plasmodium chabaudi chabaudi AS (P. chabaudi) infected red blood cells with appropriate controls. The mice were euthanased at 7, 10, 17, 26 days after malaria infection for multiparameter flow cytometry analysis. We compared P. berghei and P. chabaudi, their effects on B cells, effector and memory T cells and the outcome on BCG-induced protective efficacy against M. tuberculosis H37Rv infection by subsequent aerosol challenge. P. berghei induced a significant decrease in the frequency of central memory T cell (CD44hiCD62Lhi), marginal zone B cell (B220+AA4.1-CD1dlo), and follicular B cell (B220+AA4.1-CD1dhi ) populations. In contrast, infection with the less virulent P. chabaudi induced depletion in the marginal zone B cells but not the follicular B cells or the central memory T cells. A strong effector T cell/effector memory T cell (CD44hiCD62Lo) response enhanced by BCG vaccination was observed in both species. The reduction in the central memory T cells observed during P. berghei infection was attributed to T cell apoptosis. It should be noted that the observed changes in T cell and B cell populations described above are relative proportions of these cells among splenocytes. Surprisingly, BCG-mediated protection against M. tuberculosis H37Rv by aerosol challenge was retained in both the virulent P. berghei and less virulent P. chabaudi species despite modulations in the immune responses. We also investigated the effect of malaria infection post BCG vaccination and malaria infection prior to BCG vaccination on the cytokine responses and the efficacy of BCG vaccine both in vivo and ex vivo. Splenocytes from wild type C57BL/6 mice infected with P. yoelii 17XNL 4 weeks post BCG vaccination were analysed 13 days after P. yoelii 17XNL infection. We compared the cytokine responses and growth inhibition by MGIA in four groups of 6 mice each: naïve, BCG, BCG-malaria, and malaria control. BCG Pasteur Aeras was used as a surrogate for M. tuberculosis in the MGIA. Restimulation with PPD-T induced a significant increase in both the proportion and absolute cell numbers of CD4+ IFNγ+ and CD4+ TNF+ T cells in the BCG vaccinated compared to the naïve control. No significant differences in the proportion and cell numbers of CD4+ IFNγ+ T cells were observed between the BCG and BCGmalaria groups restimulated with PPD-T. This indicates that the presence of malaria did not significantly hamper the IFNγ response to BCG. In contrast, a significant (p<0.05) reduction was detected in the proportion of CD4+TNF+ T cells in the BCG-malaria group compared to the BCG group following restimulation with PPD-T. P. yoelii 17XNL infection also led to significant production of IL-4 by CD4+ T cells in the groups that were infected with malaria with or without BCG vaccination when restimulated with PPD-T or P. yoelii 17XNL peptide pool. Minimal production of CD4+ IL-17 T cells and CD8+ T cells were observed when restimulated with PPD-T. MGIA revealed a significant decrease in net bacterial growth (0.2 log 10) in the BCG and BCG-malaria splenocyte cultures compared to the naïve and malaria control splenocyte cultures, indicating that BCG immunized mice were able to control the growth of mycobacteria in the presence of malaria. For P. yoelii 17XNL infection prior to BCG vaccination, wild type C57BL/6 mice (n=6-11) were infected with either P. yoelii 17XNL or P. chabaudi and after 13 (acute malaria) and 21 (cleared malaria) days or 7 (acute malaria) and 28 (cleared malaria) days respectively, mice were vaccinated with BCG. They were either sacrificed 6 weeks after BCG vaccination for cytokine analysis and MGIA or challenged with M. tuberculosis H37Rv by aerosol for bacterial growth determination. BCG vaccination caused a significant increase in the proportion of CD4+ IFN-γ + and CD4+TNF+ T cells compared to the naïve control when restimulated with PPD-T. However, we observed a significant reduction in the proportion of CD4+TNF+ but not CD4+ IFN-γ + T cell responses in the acute malaria-BCG group compared to the BCG vaccinated mice following in vitro restimulation with PPD-T. Interestingly, these cytokine levels were significantly elevated upon clearance of the P. yoelii 17XNL parasites. Therefore, acute malaria infection at the time of BCG vaccination induces a transient decrease in Th1 response which is restored once the parasite is cleared. An ex vivo MGIA assay on splenocytes showed a significant decrease (0.2 log reduction) in net bacterial growth in all BCG vaccinated groups except the acute malaria-BCG group, compared to the unvaccinated groups with or without malaria. Interestingly, a significant increase in net bacterial growth was observed in the acute malaria group compared to the BCG vaccinated group, indicating that acute P. yoelii 17XNL infection prior to BCG vaccination decreases the protective efficacy of BCG in the MGIA. In an in vivo aerosol challenge with M. tuberculosis, a significant decrease was observed in bacterial burden in the spleen (0.6 log reduction) and lungs (1 log reduction) of mice that were vaccinated during acute P. chabaudi infection, vaccinated when malaria had cleared or vaccinated in the absence of malarial infection. This was further confirmed by higher numbers of acid-fast bacilli observed in all unvaccinated groups compared to all vaccinated groups with or without malaria, implying BCG vaccine efficacy is maintained in an acute or cleared P. chabaudi infection prior to BCG vaccination. This discrepancy between the in vivo aerosol challenge and ex vivo growth inhibition assay may be attributed to the different Plasmodium species with different clinical characteristics used in the study or the different kinetics in the two assays used. Conclusions Therefore, malaria parasite virulence does not inhibit the ability of BCG to control the growth of M. tuberculosis in vivo despite alterations in the immune responses. Additionally, neither Plasmodium infection prior to BCG vaccination nor Plasmodium infection post BCG vaccination abolishes the efficacy of BCG against M. tuberculosis although a decrease in CD4+ Th1 cytokine responses and concomitant increase in bacilli burdens are observed in the group of acute Plasmodium infection prior to BCG vaccination.